Pemodelan dan Simulasi Algoritma Hierarchical Token Bucket (HTB) dalam Optimalisasi Penggunaan Bandwidth pada Mikrotik - Abdulah Ardi (Riau Jurnal Teknik Informatika, 2025)
SMA Negeri 1 Alalak is a secondary school located in Handil Bakti, Alalak District, under the Ministry of Education, Culture, Research, and Technology. To support the teaching and learning process, the school has integrated digital devices (gadgets) into its curriculum, backed by a 300 Mbps internet connection. However, the lack of efficient bandwidth management has resulted in unequal network access and connectivity issues. This study aims to optimize network management by implementing the Hierarchical Token Bucket (HTB) method for bandwidth allocation. The Network Development Life Cycle (NDLC) approach is employed to ensure a structured research process, encompassing problem analysis, network topology design, implementation of the HTB method on a MikroTik RB941-2nD router, as well as system testing and evaluation. A preliminary simulation is conducted using Cisco Packet Tracer before real-world implementation. The results indicate that the HTB method effectively distributes bandwidth proportionally, allocating 1 Mbps per student for a total of 211 students and 57 teachers. Testing using Speedtest.net by Ookla reveals a decrease in speed due to bandwidth limitations; however, network access becomes more balanced and structured. Thus, the HTB method proves to be an effective solution for enhancing bandwidth management efficiency at SMA Negeri 1 Alalak.